Thermally-stable graphene metamaterial absorber with excellent tunability for high-performance refractive index sensing in the terahertz band. (December 2021) - Du, Xuemei; Yan, Fengping; Wang, Wei; Zhang, Luna; Bai, Zhuoya; Zhou, Hong; Hou, Yafei
Highlights: Hybrid elliptical graphene structure shows excellent absorptivity and large Q-factors. The absorptivity of the two bands can be up to 99.4% and 92.7%, respectively. The designed structure exhibits a high Q factor of 277.8 at 1.945 THz. The sensitivity can be up to 1.84 THz/RIU when the analyte thickness is 80 μm. Abstract: Graphene plasmons have attracted great interest for constructing high-performance functional metamaterial devices, among which graphene-based narrowband metamaterial absorbers are valuable in numerous applications. In this paper, a graphene-dielectric-metal hybrid structure is proposed to achieve dual-band excellent absorption and high-performance refractive index sensing. Numerical simulations show that the designed structure exhibits a high Q factor of 277.8 at 1.945 THz, which is higher than most previously-reported results. The sensitivity of the proposed structure can be up to 1.84 THz/RIU when the analyte thickness is 80 μm, and it exhibits promise for sensing thin-film biomolecule and thick biologic tissues. The electromagnetic field distributions show that the electromagnetic energy is highly confined in the structure at the higher order plasmon resonance, which plays an important role in achieving the excellent characteristics of the proposed structure. The tunability of the proposed structure is realized via changing the gate voltage applied to the graphene and the angles of the incident THz wave. In addition, we reveal that the proposed structure can be switched between single-band, dual-band, and 3-band absorption by tuning the incident angle under TM and TE polarization. Further results demonstrate that the proposed device possesses good thermal stability, polarization insensitivity, and outstanding fabrication tolerance. We believe that the proposed dual-band narrowband absorber can serve as a good example for other devices based on plasmons, such as selective sensors, modulators, and optical detectors.